Structural and Electrochemical Characterization of Pure LiFePO4 and Nanocomposite C-LiFePO4 Cathodes for Lithium Ion Rechargeable Batteries. (17th March 2010) - Kumar, Arun; Thomas, R.; Karan, N. K.; Saavedra-Arias, J. J.; Singh, M. K.; Majumder, S. B.; Tomar, M. S.; Katiyar, R. S.
Abstract : Pure lithium iron phosphate (LiFePO 4 ) and carbon-coated LiFePO 4 (C-LiFePO 4 ) cathode materials were synthesized for Li-ion batteries. Structural and electrochemical properties of these materials were compared. X-ray diffraction revealed orthorhombic olivine structure. Micro-Raman scattering analysis indicates amorphous carbon, and TEM micrographs show carbon coating on LiFePO 4 particles. Ex situ Raman spectrum of C-LiFePO 4 at various stages of charging and discharging showed reversibility upon electrochemical cycling. The cyclic voltammograms of LiFePO 4 and C-LiFePO 4 showed only a pair of peaks corresponding to the anodic and cathodic reactions. The first discharge capacities were 63, 43, and 13 mAh/g for C/5, C/3, and C/2, respectively for LiFePO 4 where as in case of C-LiFePO 4 that were 163, 144, 118, and 70 mAh/g for C/5, C/3, C/2, and 1C, respectively. The capacity retention of pure LiFePO 4 was 69% after 25 cycles where as that of C-LiFePO 4 was around 97% after 50 cycles. These results indicate that the capacity and the rate capability improved significantly upon carbon coating.